Are “bad” jobs bad for democracy? Precarious work and electoral participation in Europe - Azzollini, Leo; Macmillan, Ross (Frontiers in Political Science, 2023)
Introduction While socioeconomic inequality in voting has been central for research on electoral participation, recent years have seen radical changes in labor relations. The key issue is increasing prevalence of precarious work, involving dimensions as non-indefinite tenure and limited control over work activities. While occupations traditionally were the locus of political socialization, there is scarce research connecting occupational uncertainty to electoral participation. To fill this void, we develop a framework that connects the multiple dimensions of precarious work to electoral participation. Methods We test these ideas using data from 32 countries from the European Social Survey (2008–2018). Results and discussion Results indicate that work precarity is both strongly connected to traditional indicators of SES and has large, independent effects on probability of voting. We corroborate these results with heterogeneity analyses across countries. Findings show how precarious work heightens socio-economic stratification in electoral participation, undermining the universality of the right to vote and the health of democracies.